MOLECULAR DYNAMICS SIMULATIONS OF THE CAFFEIC ACID INTERACTIONS TO DIPEPTIDYL PEPTIDASE IV - ISTYASTONO, ENADE PERDANA; OCTA RISWANTO, FLORENTINUS DIKA (International Journal of Applied Pharmaceutics, 2022)
Objective: The research presented in this article aimed to examine the applicability of a recently published software PyPLIF HIPPOS to identify the interactions hotspots between dipeptidyl peptidase IV (DPP4) and its inhibitor caffeic acid during molecular dynamics (MD) simulations. Methods: Caffeic acid was docked to the binding pocket of DPP4 followed by 50 ns MD simulations, during which snapshots were taken every 10 ps. The molecular docking and the MD simulations were performed in YASARA-Structure 21.12.19. The snapshots were analyzed using the MM/PBSA analysis in YASARA-Structure and PyPLIF HIPPOS to calculate the binding energy (BE) and the caffeic acid-DPP4 interactions hotspots, respectively. Results: The 50 ns MD simulations of DPP4-caffeic acid had converged since the early stage of the simulations. The BE and the RMSD values of the ligand movement indicated a probable DPP4 allosteric site. PyPLIF HIPPOS identified 15 interacting DPP4 residues to caffeic acid. The residues interacting with caffeic acid in more than 10% snapshots of the MD simulations were Ser59, Arg61, Glu206, and Phe357. The binding residues Ser59 and Arg61 were suggested to be part of the plausible DPP4 allosteric site. Conclusion: PyPLIF HIPPOS serves as a valuable complement to the MM/PBSA method in the examination of enzyme-inhibitor interactions.